"I'm Not Going to Jail for This, " an Analysis of Anesthesia Providers' Responses to Georgia's 22-Week Abortion Ban [01I]. (May 2020) - Reeves, Jennifer A.; Goedken, Peggy; Cwiak, Carrie; Hall, Kelli
Abstract : INTRODUCTION: State-level legal regulations affect abortion provision in the United States. Anesthesia providers participate in abortion care, and their understanding of legal regulations may impact their willingness to participate in hospital-based abortion care. METHODS: In-depth qualitative interviews were conducted with currently-practicing anesthesia providers, who care for obstetric (OB) patients. A semi-structured interview guide elicited information on providers' personal abortion attitudes through case-based examples and a discussion of Georgia's (GA) 22-week abortion ban. Data were analyzed in an iterative fashion using both inductive and deductive approaches. RESULTS: Thematic saturation of the primary aim occurred after 15 interviews. Participants represented many provider types, including anesthesiologists, certified and student registered nurse anesthetists, certified anesthesiology assistants, and anesthesiology residents. Most participants practiced general or OB anesthesiology in a hospital setting (n=14). Two-thirds of participants reported prior participation in abortion (n=10). Most providers had little to no prior knowledge of GA's 22-week abortion ban (n=11) and perceived an overall neutral or negative impact of the law on OB practice (n=13). Prominent themes that emerged from the data included "fear of criminality, " "transfer of responsibility to the law, " and "retroactive versus proactive medical care, " which described how anesthesia providers reacted to state-specific legislation on abortion. CONCLUSION: Anesthesia providers are not well-informed of state-specific abortion legislation and demonstrate a mixed response to such laws. After introduction of GA's 22-week ban, many participants reported a more conservative approach to participating in hospital-based abortion care, which affects abortion access in this setting.